SELF-REGULATION IN LEARNING ENGLISH BEYOND THE CLASSROOM AMONG STUDENTS AT UIN SUSKA RIAU - Hasibuan, Sari Alum; Nuardi, Nuardi (Journal of English and Arabic Language Teaching, 2025)
This research aimed to describe the level of self-regulation in English learning beyond the classroom and identifying the most dominant dimension among English Education students at State Islamic University of Sultan Syarif Kasim Riau. Quantitative descriptive method was used in this research. 129 fourth-semester students were the population of this research, and 60 students were selected with simple random sampling. Data were collected with questionnaire adapted from Zheng et al. (2016), covering six dimensions of self-regulation goal setting, environmental organization, time management, task strategy, help-seeking, and self-evaluation. The research findings showed that the level of student self-regulation was in high category. Most students (61.67%) were able to independently plan, organize, and monitor their English learning beyond the classroom. The most dominant dimension was goal setting (M = 3.22), indicating that students were able to set clear learning goals. However, some students still needed to increase their abilities of time management and self-evaluation. Overall, students at State Islamic University of Sultan Syarif Kasim Riau had excellent self-regulation learning ability.